2016
DOI: 10.1371/journal.pone.0167564
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Amendments on the Physical Properties of Soil under Tropical Long-Term No Till Conditions

Abstract: Tropical regions have been considered the world’s primary agricultural frontier; however, some physico-chemical deficiencies, such as low soil organic matter content, poor soil structure, high erodibility, soil acidity, and aluminum toxicity, have affected their productive capacity. Lime and gypsum are commonly used to improve soil chemical fertility, but no information exists about the long-term effects of these products on the physical attributes and C protection mechanisms of highly weathered Oxisols. A fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Similar to the results of Ahmad et al [38], we found that soil water NO 3 -N concentrations were higher in Poamoho than in Waimānalo for depths of 30 and 60 cm. The increased leaching at Poamoho could be due to the differences in soil physical and mineral properties between the two locations [39]. Nitrate-nitrogen losses were reduced by 20% at Waimānalo and 40% at Poamoho when MBM was applied in split applications compared to a single preplant application.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to the results of Ahmad et al [38], we found that soil water NO 3 -N concentrations were higher in Poamoho than in Waimānalo for depths of 30 and 60 cm. The increased leaching at Poamoho could be due to the differences in soil physical and mineral properties between the two locations [39]. Nitrate-nitrogen losses were reduced by 20% at Waimānalo and 40% at Poamoho when MBM was applied in split applications compared to a single preplant application.…”
Section: Discussionmentioning
confidence: 98%
“…Rice breeding programs need to incorporate NuUE traits as this helps resource-poor farmers to save on fertilizer, and allows maximization of valuable resources to increase profitability. To date, several morphological and agronomic traits have been identified, and they can be used as indicators of nitrogen (N) [ 52 , 64 , 65 , 66 ], phosphorus (P) [ 7 , 38 , 67 , 68 , 69 , 70 ], and potassium (K) [ 16 , 39 , 40 , 71 , 72 , 73 ] deficiency tolerance under both field and hydroponic conditions. Using different genetic backgrounds of mapping populations, such as RILs, NILs, BILs, ILs, CSSLs, DHs, and BC 2 F 4 , there are several reports on QTL identification with independent studies of low-N, -P, and -K conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The post planting soil physical properties were observed to be improved by the application of amendments [7]. Soil physical properties contribute to water and nutrient activities, soil temperature, aeration, nutrient cycling, and root growth which affect yield of crops [8,9].…”
Section: Discussionmentioning
confidence: 99%